Genetic variations underlying Gilbert syndrome and HBV infection outcomes: a cross-sectional study - Yao, Bilian; Xu, Qi; Zhang, Xinxin; Han, Yue (Frontiers in Genetics, 2023)
Background: Constant cellular damage causes a poor prognosis of hepatitis B virus (HBV) infection. Accumulating evidence indicates the cytoprotective properties of bilirubin. Here, we investigated the association of UDP glucuronosyltransferase family 1 member A1 (UGT1A1), the genetic cause of Gilbert syndrome (GS), a common condition of mild unconjugated bilirubinemia, with HBV infection outcomes. Methods: Patients (n = 2,792) with unconjugated hyperbilirubinemia were screened for HBV infection and host UGT1A1 variations in Ruijin Hospital from January 2015 to May 2023, and those with confirmed HBV exposure were included. The promoter/exons/adjacent intronic regions of UGT1A1 were sequenced. HBV infection outcomes were compared between hosts with wild-type and variant-type UGT1A1. The effect magnitudes of UGT1A1 variations were evaluated using three classification approaches. Results: In total, 175 patients with confirmed HBV exposure were recruited for final analysis. Age, gender, level of HBV serological markers, and antiviral treatment were comparable between UGT1A1 wild-type and disease-causing variation groups. Five known disease-causing mutations (UGT1A1*28, UGT1A1*6, UGT1A1*27, UGT1A1*63, and UGT1A1*7) were detected. The incidence of cirrhosis or hepatocellular carcinoma (LC/HCC) was significantly lower in UGT1A1 variant hosts than in UGT1A1 wild-type hosts (13.14% vs. 78.95%, p < 0.0001). The rarer the UGT1A1 variation a patient possessed, the higher the age at which LC/HCC was diagnosed (R = 0.34, p < 0.05). In contrast, patients without cirrhosis achieving HBsAg clearance were identified only in the UGT1A1 variant group (12.32% vs. 0%). Conclusion: The findings of this study provide insights into the association between preexisting genetically mild bilirubin elevation and viral infection outcome. We showed that the accumulation of UGT1A1 variants or the rarity of the variation is associated with a better prognosis, and the effect magnitude correlates with UGT1A1 deficiency. This study demonstrates the therapeutic potential of host UGT1A1 variations underlying GS against HBV infection outcomes.